2005
DOI: 10.1177/0021998305052037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flexural Properties of Syntactic Foam Core Sandwich Composites and Effect of Density Variation

Abstract: Microballoons (hollow particles) of the same outer radius but with five different inner radius values are used to fabricate five types of syntactic foam slabs. These five types of slabs are used as the core material to fabricate sandwich composites. Three- and four-point bending and short beam shear strength tests are carried out to characterize the flexural behavior of syntactic foam core sandwich composites. The effect of change in microballoon radius ratio (ratio of the inner to the outer radius) on the fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 20 publications
5
61
0
1
Order By: Relevance
“…In general, the specimens can fracture under two types of loads, horizontal load and vertical load. Hence, crack location and propagation directions can give an evaluation in determining the type of load that causes specimen failure [16]. It was observed that in all specimens, the failure process can be observed in the tensile side firstly and then followed by a sudden (NSF) or slow (SF-WKSF) failure.…”
Section: Flexural Properties Of Sf-wksf and Neat Syntactic Foammentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the specimens can fracture under two types of loads, horizontal load and vertical load. Hence, crack location and propagation directions can give an evaluation in determining the type of load that causes specimen failure [16]. It was observed that in all specimens, the failure process can be observed in the tensile side firstly and then followed by a sudden (NSF) or slow (SF-WKSF) failure.…”
Section: Flexural Properties Of Sf-wksf and Neat Syntactic Foammentioning
confidence: 99%
“…Many researchers have investigated the flexural properties of various syntactic foams [3][4][5][6]. Results of these researches showed that the addition of microballoons could reduce the densities of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Syntactic foams have completely closed cells and therefore absorb water to a lesser degree compared to conventional foams which have open-cell structure [50,73,74,77,80]. Moisture absorption in syntactic foams is affected by a large number of parameters.…”
Section: Features Of Syntactic Foamsmentioning
confidence: 99%
“…Gupta et al [2] studied the behavior of sandwich-structured composites with syntactic foam core under three-point bending for both beams with large (16:1) and short (5:1) aspect ratio and gave a method to analyze failure of these structures. Gupta et al [3] studied the effect of microballoon radius ratio on the flexural properties of sandwich composites with syntactic foam core and their results show that in three and four point bending the radius ratio does not have any effect on the failure of the beam. They also gained the result that in case of shear failure in short beam shear test microballoon radius ratio plays an important role in determining the strength of the sandwich.…”
Section: Introductionmentioning
confidence: 99%